Community Connectors (CCx): the strategies employed by peer to peer connectors to foster relationships with early years caregivers to improve universal early child health and development - C. F. Mills; E. Lowrie; K. Kinloch; E. Hall (BMC, 2021)
Abstract Blackpool is one of the most deprived Local Authority (LA) areas in England; in April 2015 the Blackpool Better Start (BBS) Partnership was allocated £45 million over 10 years from the Big Lottery Fund (BLF) as one of five 'A Better Start' initiative areas in England. The aim of the 'A Better Start' initiative is to improve outcomes for children from conception to 3 years of age. Co-designed by professionals and the community, the Community Connector (CCx) programme employs residents to directly engage caregivers of children, in seven of Blackpool's most socio-economically deprived wards. The CCx follow a socioecological framework which proposes that caregivers will be positively influenced to engage in early years activities because of connections to trained peers. Peer support models are commonly applied within targeted early years health settings (i.e., infant feeding support, literacy) yet their role to improve child outcomes at a universal level has received little attention. This paper focuses on caregiver-level evidence of the strategies employed by CCx - part of an early stage pilot study supported by Frontiers of Innovation, the Harvard Centre on the Developing Child's Research and Development platform. The study collated attendance data from Children's Centres, these are publically funded community centres providing information and activities for families with children 0-5 years of age. The study data included individual interactions between a CCx and caregiver over a 1 year period (1st April 2018 - 31st March 2019). A sampling frame was created from which a total of 22 interviews with caregivers were undertaken in early years community settings. The interview data was thematically analysed; the findings highlighted the mechanisms by which CCx served to mediate service and caregiver communication boundaries, negotiate access to spaces, and encouraged sustained engagement in longer term activities such as volunteering and training. Value was embedded by the CCx in their process of establishing and maintaining connections with caregivers through the 'everyday' conversations, their individualised approach and in demonstrating self-efficacy behaviours. Further research is required to review the impact of the CCx role in caregiver's recall of early years information, nevertheless the study provided important learning for establishing formalised CCx programmes elsewhere, and has implications for community health and early years policy and practice.